The importance of intellectual capital management in the knowledge-based economy - Hamzah, N.; Ismail, M.N. (2008)
An organisation's intellectual capital is said to be a source of competitive advantage and there is evidence that business success can be partly explained by its intellectual capital. Previous literature argues that the difference between the organisation's market value on the stock exchange and its book value is depends on its intellectual capital. This is a conceptual paper and it discusses on the importance of intellectual capital management to an organisation strategic management process. This study uses case study method in order to examine whether there is a linkage between an organisation's business strategy and its intellectual capital management. This study argues that intellectual capital management should be injected in an organisation's strategic management process as the implementation parts. At the end of this paper, this study proposes typology that explains the linkage between business strategy and intellectual capital management.